Effect of Lap Length and Stiffness of Peel-Stop Fasteners in Single Lap Joints - Atsushi Takano; Chao Li; Ryuta Kitamura (Applied Sciences, 2021)
Strength tests on single lap joints with one adhesive (AV138/HV998) and one adhesive layer thickness (0.5 mm), three peel stoppers (brass bolt, nylon bolt and steel pin), and four lap lengths (12.5 mm, 25 mm, 40 mm and 100 mm) were conducted to investigate the effects of varying the lap length and stiffness of the peel-stop fasteners. Joint failure stress decreased, but failure force increased with lap length. Furthermore, joint failure stress was higher with the peel stopper. The effect of the brass-bolt peel stoppers was significant, whereas the effects of the nylon bolts and steel pins were smaller than that of the brass bolts. This indicates that the axial clamp strength and stiffness of the peel stopper are important factors in the shear strength of the lap. In addition, the effect of the stopper was negligible for the 12.5 mm lap. The reason is that the shear strength in the case of the 12.5 mm lap was large and thus the effect of the peel stopper was comparatively small. Moreover, the strength of the 100 mm lap reached the adherent material’s strength.